Relationship between working capital management and the performance of firm in different business cycles - Maryam Pakdel; Majid Ashrafi (Dutch Journal of Finance and Management, 2019)
Working capital management is one of the issues that plays an important role in the management structure of an organization and as one of the main force moving forward organizations, it is important to obtain huge economic benefits. This study focused on the relationship between working capital management and the performance of firm in different business cycles. A sample consist of 80 companies listed in Tehran Stock Exchange from 2002 to 2013 have been selected. In this study, the cash conversion cycle is considered as a measure of working capital management, which consists of days account receivable, days inventory and days account payable. Hypotheses of this study were analyzed using panel method data and the results show that there is a significant negative relationship among the management of working capital and firm performance. Among the components of cash conversion cycle, only day's account receivable has negative and significant relationship with firm performance. The results also show that the various business cycles do not modify the relationship between working capital management and the performance of companies.
Keywords: 650; working capital management; days account receivable; days inventory; days account payable; performance